Involvement of Histamine in Endothelium‐Dependent Relaxation of Mesenteric Lymphatic Vessels. (October 2014) - Nizamutdinova, Irina Tsoy; Maejima, Daisuke; Nagai, Takashi; Bridenbaugh, Eric; Thangaswamy, Sangeetha; Chatterjee, Victor; Meininger, Cynthia J.; Gashev, Anatoliy A.
Abstract Objectives The knowledge of the basic principles of lymphatic function, still remains, to a large degree, rudimentary and will require significant research efforts. Recent studies of the physiology of the MLVs suggested the presence of an EDRF other than NO. In this study, we tested the hypothesis that lymphatic endothelium‐derived histamine relaxes MLVs. Methods We measured and analyzed parameters of lymphatic contractility in isolated and pressurized rat MLVs under control conditions and after pharmacological blockade of NO by l‐NAME (100 μM) or/and histamine production by α‐MHD (10 μM). Effectiveness of α‐MHD was confirmed immunohistochemically. We also used immunohistochemical labeling and Western blot analysis of the histamine‐producing enzyme, HDC. In addition, we blocked HDC protein expression in MLVs by transient transfection with vivo‐morpholino oligos. Results We found that only combined pharmacological blockade of NO and histamine production completely eliminates flow‐dependent relaxation of lymphatic vessels, thus confirming a role for histamine as an EDRF in MLVs. We also confirmed the presence of HDC and histamine inside lymphatic endothelial cells. Conclusions This study supports a role for histamine as an EDRF in MLVs.